Implementasi Algoritma Playfair Cipher dan Least Significant Bit pada Citra Digital - Hermansa; Rusydi Umar; Anton Yudhana (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Message security is very important now. Because security is part of the privacy of someone who wants to protect messages from those who do not have the right to read or receive them. The method used for securing information messages with message encryption and decryption techniques is the Playfair Cipher algorithm combined with the Least Significant Bit (LSB) method. In this study it was found that the Playfair Cipher algorithm is quite safe in implementing cryptographic encryption or ciphertext because the playfair cipher has a level of appearance of letters that is so difficult to predict so that the ciphertext becomes a randomized collection of data. For the Least Significant Bit (LSB) steganography method in the insertion of a secret or embedded message it is difficult to guess in plain view the changes that occur between before and after the image is inserted are not too significant. Also see the value of the Peak-Signal-to-Noise ratio or PSNR can still be considered good quality due to> 30 decibels (dB). So the final result of the combination of the Playfair Cipher algorithm with the Least Significant Bit (LSB) method is quite good in securing messages.